MANAGEMENT OF THE PROTECTION OF MOVABLE CULTURAL PROPERTY AND EXTREME SITUATIONS: A CASE STUDY OF TWO LITHUANIAN MEMORY INSTITUTIONS - Dacytė, Gerda Sigita (Knygotyra, 2017)
The aim of the article is to analyze international and local legal instruments regarding the protection of movable cultural heritage. It also highlights the importance of instructions and orders of ministerial departments related to the protection of cultural heritage. Furthermore, the article provides a research-based analysis regarding the management of emergency situations and the protection measures of movable cultural property in the Wroblewski Library of the Lithuanian Academy of Sciences and National Museum Palace of the Grand Dukes of Lithuania. The research was based on the comparative case study method, which makes it possible to focus on and delve deeply into the essence of a single problem. The research was conducted using a questionnaire and a structured interview, during which two respondents from memory institutions were interviewed. The answers, provided by the respondents, help to determine the possibility of practical implementation of the objectives raised in the legal acts of the Republic of Lithuania regarding the protection of cultural property. Emphasized in the research is identification of threats, allocation of responsible personnel, enactment of preventive measures and the importance of establishing and implementing specific actions on both theoretical and practical levels.